2014
DOI: 10.4103/2278-330x.130443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protective effect of myricetin, a bioflavonoid in dimethyl benzanthracene-induced breast cancer in female Wistar rats

Abstract: Background:Breast cancer is one of the most common cancers worldwide. Alarmingly, the incidence of breast cancer is rising rapidly in India.Aim:The present research was focused to assess the role of myricetin; a bioflavonoid in 7,12-dimethylbenzanthracene (DMBA)-induced breast cancer in female Wistar rats.Materials and Methods:A total of 36 female Wistar rats (total 6 groups, n = 6 per group) 6 - 8 weeks old, weighing 150 gm were used in the study. DMBA was given at the dose of 7.5 mg/kg subcutaneously in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, myricetin is nearly insoluble in water [13,14], leading to low bioavailability. Thus, myricetin is usually administered orally as aqueous suspensions, reducing its clinical applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, myricetin is nearly insoluble in water [13,14], leading to low bioavailability. Thus, myricetin is usually administered orally as aqueous suspensions, reducing its clinical applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…[32]. The dietary intake of myricetin from our foods is about 0.98-1.1 mg per day, which is quite higher than some other flavonols [33]. Recent studies showed that myricetin is an antioxidant and it possesses cytoprotective, anticarcinogenic, antiviral, and antimicrobial effects [34].…”
Section: Myricetinmentioning
confidence: 97%
“…A recent study showed that microemulsion formulation can improve the solubility of myricetin 1225 times greater than water and also enhance its anti-proliferative activity against human liver cancer cells (HepG2) [92]. Myricetin is a promising anti-carcinogen and chemo preventive agent with therapeutic potential reported in ovarian [93], colon [94], skin [95], liver [96] and breast [97] cancers. Cell-based studies have shown that myricetin inhibited proliferation of T24 bladder cancer cells by inducing cell cycle arrest at the G2/M phase by downregulating cyclin B1 and cyclin-dependent kinase cdc2 [98].…”
Section: Myricetinmentioning
confidence: 99%